Microbial Parameters as Predictors of Heterotrophic Prokaryotic Production in the Ross Sea Epipelagic Waters (Antarctica) during the Austral Summer - Luis Salvador Monticelli; Gabriella Caruso; Filippo Azzaro; Maurizio Azzaro; Rosabruna La Ferla; Giovanna Maimone; Paolo Povero; Alessandro Cosenza; Renata Zaccone (Journal of Marine Science and Engineering, 2022)
A regression-based approach was used to test the suitability of a range of parameters, including total prokaryotic cell abundance and biomass, as lipopolysaccharide (LPS) content, and exoenzymatic activities (leucine aminopeptidase, LAP, beta-glucosidase, ß-G, and alkaline phosphatase, AP) as predictors of heterotrophic prokaryotic production (HPP) in the Ross Sea epipelagic waters. A close association between HPP and protein hydrolysis mediated by enzymatic activity (LAP), and to a lower significance level with the other variables, was recorded. Three multiple regression equations were developed from two microbial datasets collected during middle austral summer periods. All showed a good predictive ability for HPP, and this was further validated through a comparison between the predicted and the observed HPP values. The obtained regression equations proved to represent a promising example of empirical models for further predictive studies in the Ross Sea where—through the incorporation of additional microbiological and environmental parameters—the developed models could find a practical application to cover the entire austral summer period.